Value Creation in Leveraged Buyouts - Audrlický, Dan (2025)
This master thesis analyses value creation in leveraged buyouts (LBOs). Combination of structured review of academic and practitioner literature with following in-depth case study of Micromed is implemented. Micromed is an Italian neurodiagnostics company operating within European med-tech mid-market and was acquired by the healthcare-specialist sponsor ArchiMed in 2016 and exited in 2023 via trade sale to Natus Medical. The deal economics were not disclosed and for the reconstruction we use registry data, financial statements and sector benchmarks as anchors for establishment of entry and exit economics. These economics are used for equity bridge decomposition at equity-level and simplified Created Value Attribution (CVA-lite) model at enterprise-level which provide useful information about components responsible for value creation. Based on case reconstruction and after we account for follow-on equity used to finance bolt-on acquisitions, we approximate that the deal generated 2.7× multiple on invested capital and 23–24 % internal rate of return with majority of value created attributed to EBITDA growth and firm-specific outperformance “alpha”. Multiple uplift contributed moderately, and deleveraging only as a minor share of value created. These findings support the view that among European mid-market healthcare buyouts, operational and strategic transformation are primary drivers of sustainable value creation, while leverage depending on credit market conditions and market-driven valuation changes play a secondary role. The thesis also shows that using public data under conditions of limited disclosure can yield meaningful insights into LBO value creation.